Buya Hamka’s Concept of Zuhud in Facing Hedonism - Muhammad Iqbal Oki Akbar; Nur Hadi Ihsan (Penerbit Hellow Pustaka, 2026)
This article examines the concept of zuhud introduced by Buya Hamka as a response to the phenomenon of hedonism in modern society. Buya Hamka, a prominent Muslim scholar and intellectual, put forward the zuhud view that can be a guide to deal with the hedonistic lifestyle that is currently struck. In this article, we delve into the thought of Buya Hamka, elaborate on the concept of zuhud that he carries, and analyze its relevance in overcoming the challenges of hedonism in the contemporary era. Buya Hamka, as a figure who combines a balance between spirituality and intellect, offers a zuhud view that invites individuals to stay away from hedonistic tendencies that can destroy moral values. His concept of zuhud encourages understanding of true needs and limits worldly passions in order to achieve ultimate happiness. Thus, this research contributes to the understanding of how the concept of zuhud Buya Hamka can be a significant alternative